Standardization Project of China’s Spoken National Language from the late Qing Dynasty to the End of the Republican Period: A Literature Review - Liukkonen, Meri (My University, 2024)
The topic of this bachelor’s thesis is the standardization project of China’s spoken language from the late Qing dynasty to the end of the republican period. This thesis is a literature review, and it uses as its reference fields studies, non-fiction books and articles. The goal is to showcase different stages of the national language project and analyze the politics, phenomena and ideologies that are connected to it. Additionally, this thesis will take a closer look at China’s national language’s relationship with Mandarin Chinese and the national language’s artificiality. The literature review will be thematic, it will utilize the research methodologies of sociolinguistics, and it will focus on language politics and language planning. Analysis shows how the connection between China’s national language and modernization is very close and how the spoken national language was seen as a crucial mean of modernization during its time. A top-down type of approach and the national language’s goal to be a language for the people can be seen as an important special feature, especially compared to the formation of other national languages. Additionally, it was discovered how the connection between the national language and nationalism divides opinions in the field. The debate is over the question of how much Han-nationalistic ideology has affected the formation of the national language compared to purely pragmatic thinking. In the papers researched, there are also comments on how no non-Han languages were considered to become the national language, the lack of China-centric research methodologies and sociolinguistics being Eurocentric. The last major find is the indefiniteness of the terms Guoyu and Guanhua, and their connection to each other in the papers researched. Additionally, as seen in the referenced papers, language prestige was an important part of the choosing process of the national language. This paper’s findings and showcased gaps and debates in the field could work as a possible helping guideline in the research of China’s national language and in evaluating the need for new research methods. Additionally, this thesis could help with understanding the current state of China’s national language, for example, its language politics and linguistic history.

Tämän kandidaatintutkielman aihe on Kiinan puhutun kansalliskielen muodostuminen Qing-dynastian lopusta tasavaltalaisajan loppuun. Kandidaatintutkielma on kirjallisuuskatsaus, jonka aineistona on alan tutkimuksia, tietokirjoja, sekä artikkeleita. Tavoitteena on muodostaa kuva kansalliskieliprojektin eri vaiheista sekä käydä läpi ja analysoida siihen liittynyttä politiikkaa, ilmiöitä ja ideologioita. Lisäksi tutkielmassa tarkastellaan Kiinan kansalliskielen ja mandariinikiinan suhdetta sekä kansalliskielen keinotekoisuutta. Kirjallisuuskatsaus etenee temaattisesti ja siinä hyödynnetään sosiolingvistiikan tutkimusperiaatteita ja keskitytään kielistandardisaatioon sekä kielipolitiikkaan ja kielisuunniteluun. Tarkastelu osoittaa, että Kiinan kansalliskielen ja modernisaation yhteys on hyvin läheinen, ja että puhuttu kansalliskieli nähtiin modernisaation onnistumisen kannalta tärkeäksi tekijäksi aikalaisnäkökulmasta. Ylhäältä alas (top-down) -lähestymistapa sekä kansalliskielen tavoite olla koko kansan kieli nähdään merkittävänä erikoispiirteenä Kiinan kansalliskielen muodostumisessa verrattuna muihin kansalliskieliin. Lisäksi tarkastelussa huomattiin, kuinka kiinan puhutun kansalliskielen ja nationalismin yhteys on merkittävä väittelyn aihe alalla. Mielipiteitä jakaa kysymys siitä, kuinka paljon Han-nationalistinen ideologia on ollut vaikuttavana tekijänä kielen muodostumisessa verrattuna puhtaasti pragmaattiseen ajatteluun. Tarkastelluista aineistoissa on kommentoitu myös Kiinan muiden kuin Han kielten vähäistä käsittelyä kansalliskielten valinnassa, kiinakeskeisten tutkimusmenetelmien puutetta ja sosiolingvistiikan eurosentrismiä. Edellisten lisäksi viimeinen merkittävä huomio on termien Guanhua ja Guoyu epämääräinen käsittely aineistoissa sekä näiden historiallinen yhteys toisiinsa. Lisäksi tutkimusaineistosta voidaan havaita, että tärkeä osa kansalliskielen valintaa on ollut kieliprestiisiyden painottaminen. Tämä kandidaatintutkielman löydöt, sekä nostamat puutteet ja väittelyt voivat toimia mahdollisena apuna Kiinan kansalliskielen tutkimisessa ja uusien tutkimustapojen tarpeen arvioimisessa. Lisäksi tutkielma voi toimia apuna Kiinan kansalliskielen nykytilan ymmärtämiseen, kuten kielipolitiikan tai lingvistisen historian suhteen.
Keywords: national language, national spoken standard, Guoyu, Guanhua, nationalism, standardization, Chinese sociolinguistics, reform, language policies, modernization